How to achieve cost savings and strategic performance in purchasing simultaneously: A knowledge-based view. Issue 2 (March 2020) - Schütz, Kai; Kässer, Matthias; Blome, Constantin; Foerstl, Kai
Abstract: The competitive advantage purchasing provides has been debated for decades. For a novel perspective we derive a theoretical framework grounded in the knowledge-based view in order to examine how purchasing knowledge and purchasing integration impact cost and strategic performance. The derived hypotheses are tested based on extensive secondary data from a large European multinational utility company. The 179 studied 'purchasing-internal client relationships' contain real contracted savings data and internal client ratings of purchasing knowledge, purchasing integration and strategic purchasing performance. We show that purchasing knowledge is a major antecedent for both savings and strategic purchasing performance. This effect is further amplified by purchasing integration. With this study, we extend the understanding of the purchasing knowledge–performance link. We conclude that purchasing knowledge becomes particularly valuable when combined with other functions' processes through purchasing integration. This causal chain is also supported through general knowledge-based view theory. Moreover, we provide numerical evidence of the value of knowledge creation and integration processes to purchasing professionals in our managerial implications based on results obtained from actual purchasing savings data. Highlights: Purchasing knowledge as major antecedent of purchasing performance. Support of knowledge-based advantages that are amplified by purchasing integration. Strategic purchasing performance leads to positive savings performance. Extensive data base of real contracted savings. Evaluation of purchasing according to the internal client.